PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH (ZPT) TERHADAP PERTUMBUHAN STUM MATA TIDUR KARET (Hevea brasiliensis Muell Arg.) KLON IRR 112 - Yuliantina Azka; Meriyanto Toyib; Muhammad Darmawi (Universitas Tridinanti Palembang, 2016)
This study aimed to assess the effect of plant growth regulator on the growth ofthe eye stum IRR rubber bed 112. This research was conducted in the village of SungaiRengit, District Talang Kelapa, Banyuasin Regency, Sumatera Selatan Province. Thestudy was conducted from May 2014 through the month of August 2014. This study useda randomized block design (RBD) with 6 treatments and 4 replications. The treatmentsstudied were: B0 = 0 ml / Control, B1 = 4 ml / l of water, B2 = 8 ml / l of water, B3 = 12ml / l of water, B4 = 16 ml / l of water, and B5 = 20 ml / l of water. Each treatmentconsisted of 10 plants, the sheer number of plants that diteiti much as 240 plants (poybag)for a total of as many as 24 treatments and replications treatment. Each unit (unit)treatment trials, there are 3 (three) plant sample. Parameter observation that the speed ofgrowth of shoots (hst), shoot length (cm), number of petiole (strands), the percentage ofseedlings grown (%), weight of wet berangkasan plant (g), berangkasan dry weight ofplants (g), weight of wet roots departure (g), root dry weight berangkasan (g) and leafarea (cm). Based on the results obtained it can be concluded that, an organizing treatmentconcentration Grow 12 ml / 1 water tends to give the best results on shoot length, rootfresh weight and root dry weight.Keyword : eye stum IRR rubber bed, plant growth regulator, Hevea brasiliensis MuellArg. klon IRR 11